2021
DOI: 10.2500/aap.2021.42.200113
|View full text |Cite
|
Sign up to set email alerts
|

Primary immunodeficiency diseases treated with immunoglobulin and associated comorbidities

Abstract: Background: Primary immunodeficiency diseases (PIDD) consist of a heterogeneous group of disorders characterized by various aspects of immune dysregulation. Although the most universally recognized manifestation of PIDD is an increased susceptibility to infections, there is a growing body of evidence that patients with PIDD often have a higher incidence of lung disease, autoimmunity, autoinflammatory disorders, and malignancy. Objective: The purpose of this study was to better understand the noninfectious co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Data on the estimated prevalence of asthma and COPD in patients with primary immunodeficiency vary significantly. In a retrospective US insurance claims database analysis from 2021, Dilley et al [49] report a prevalence as high as 51.5% for asthma and/ or COPD. However, the relevance of data collection is exemplified by a recent single-center study by de Wit et al [50] In this cohort of 253 mostly adult primary antibody deficient patients, the prevalence of obstructive lung disease was 56% when using patient questionnaires as the data source, and dropped to 16% when only including patients with diagnosis confirmed by pulmonary function testing.…”
Section: Asthma and Chronic Obstructive Pulmonary Disease: Epidemiolo...mentioning
confidence: 99%
“…Data on the estimated prevalence of asthma and COPD in patients with primary immunodeficiency vary significantly. In a retrospective US insurance claims database analysis from 2021, Dilley et al [49] report a prevalence as high as 51.5% for asthma and/ or COPD. However, the relevance of data collection is exemplified by a recent single-center study by de Wit et al [50] In this cohort of 253 mostly adult primary antibody deficient patients, the prevalence of obstructive lung disease was 56% when using patient questionnaires as the data source, and dropped to 16% when only including patients with diagnosis confirmed by pulmonary function testing.…”
Section: Asthma and Chronic Obstructive Pulmonary Disease: Epidemiolo...mentioning
confidence: 99%
“…The clinical presentation of PID, and one of the most common symptomatic primary immune deficiency disorders, common variable immune deficiency (CVID) is broad and may present as predominantly recurrent infections or may present with autoimmune, inflammatory conditions or malignancy. 3 , 4 Secondary immune deficiency is more common than PID, and may present within a wider range of specialties and is associated with an increased risk of infection. 5 Calculated globulin may be low in hypogammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…IVIg, containing the full range of antibody spectrum, is derived from the plasma of thousands of healthy donors. It has been used to treat patients with autoimmune diseases for decades [15][16][17][18]. Moreover, it has been demonstrated that in addition to anti-amyloid-β (Aβ), IVIG also has anti-in ammatory and immunomodulatory functions [19][20][21].…”
mentioning
confidence: 99%